ХУБИЛАЙ ХААН БА МОНГОЛ ГҮРНЭЭС АЗИ НОМХОН ДАЛАЙН БҮС НУТАГТ ЯВУУЛСАН ЦЭРЭГ, УЛС ТӨРИЙН БОДЛОГЫН ЗАРИМ АСУУДАЛ - Д.Галбаатар, (Politology, 2023)
The author describes political agenda, practical reasons and relevance, and diplomatic policy beyond two large-scale invasions by Khubilai Khaan towards Japanese islands within Pacific region. The primary goal of this warfare was to perform on-land tactic army 'training', not to invade Japan, as documents suggest.